Doing Business 2004 : understanding regulation (World Bank Group, 2004)
Since 2004 Doing Business has tracked regulatory reforms aimed at improving the ease of doing business in the world’s economies. Doing Business 2006, the third report in the series, found that Eastern European nations were aggressively courting entrepreneurs with far-reaching reforms to streamline business regulations and taxes, but African and Middle Eastern nations with high youth unemployment rates continued to thwart small and medium businesses with heavy legal burdens and piecemeal reforms.